If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 7 = 10x + 17 Reorder the terms: 7 + 12x = 10x + 17 Reorder the terms: 7 + 12x = 17 + 10x Solving 7 + 12x = 17 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 7 + 12x + -10x = 17 + 10x + -10x Combine like terms: 12x + -10x = 2x 7 + 2x = 17 + 10x + -10x Combine like terms: 10x + -10x = 0 7 + 2x = 17 + 0 7 + 2x = 17 Add '-7' to each side of the equation. 7 + -7 + 2x = 17 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 17 + -7 2x = 17 + -7 Combine like terms: 17 + -7 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 0.40x+0.05(6-x)=0.10(-32) | | 12.8=4b | | 236-3x=33x+24 | | 10-8x=170-36x | | 2(x+2)=2(x+8) | | -145-8x=10x+17 | | 2x+11=-69-8x | | 85-4x=14x+23 | | 3(x-3)(x+1)=(2x-1)(x-1)+8 | | 12-8x=102-29x | | 3x+1=-(x-5) | | 2(y+8)=7x-2 | | 113-2x=5x+15 | | -53-10x=7x+15 | | -35-5x=5-10x | | 6x^2+33x-18=0 | | 0.333k-4=9 | | 4m+7m=55 | | 4x=7x | | 72-4x=2x+6 | | 14a+14b+6c+2c-2b-6a= | | (n+5)*5=55 | | 7-x^2=4x | | a=-5+4b | | -6-3x=9-8x(1dp) | | 13p+19q+p-5q-5p= | | -6-3x=9-8x | | 5x(2x-1)-(2x-1)=0 | | 2k^2-3k-1=0 | | 2a-9=-5 | | 2(x+8)=6x-4 | | 4x+2.14x=3.49x |